Kaedah Soal Jawab Dalam Pengajaran Imam Abu Anifah: Satu Analisis Perbandingan - Mohd Anuar Mamat (Universiti Sains Islam Malaysia, 2024)
Method of teaching is an important element in the process of education. It is closely related to the effort towards a realization of quality education and effective teaching. This article presents the questioning method as one of the teaching method employed by Abfi Hanifah. The discussion is based on a selection of his treatises and his teaching practice thereof. This article found that the questioning method according to Abu Hanifah is in accordance with the Islamic tradition which is derived from al-Quran, al-Sunnah and the practice of the Companions. It is developed later by the scholars of Islam.